PELATIHAN LOGOANALISIS UNTUK MENINGKATKAN RESILIENSI PADA PENDERITA DIABETES MELITUS (DM) TIPE 2 - NURMAULIA KHOTMI (Universitas Islam Negeri Mataram, 2019)
Diabetes mellitus (DM) is caused by disruption of insulin production produced by the pancreas gland or lack of responsiveness of body cells to insulin. In addition, DM is also caused lifestyle that is not healthy. Diabetics are recommended for lifelong treatment, which causes many patients who experience boredom, expensive fees and emotional changes cause the subject to experience stress. Stress is likely to occur due to low resilience in these patients. The purpose of this study was to examine the effect of training on logoanalysis to improve resilience in type 2 diabetes mellitus. This study used a single case design with ABAB design. Measurement of resilience using scale from Wagnild & Young (1993) with reliability coefficient of 0.902. Hypothetical testing is done quantitatively using visual inpection and qualitative techniques. This study is that the training of logoanalysis effective to increase resilience in people with type 2 diabetes mellitus.